2014
DOI: 10.1016/j.molmet.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

ER calcium release promotes mitochondrial dysfunction and hepatic cell lipotoxicity in response to palmitate overload

Abstract: Palmitate overload induces hepatic cell dysfunction characterized by enhanced apoptosis and altered citric acid cycle (CAC) metabolism; however, the mechanism of how this occurs is incompletely understood. We hypothesize that elevated doses of palmitate disrupt intracellular calcium homeostasis resulting in a net flux of calcium from the ER to mitochondria, activating aberrant oxidative metabolism. We treated primary hepatocytes and H4IIEC3 cells with palmitate and calcium chelators to identify the roles of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 37 publications
6
123
1
1
Order By: Relevance
“…Most importantly, we found that calculated oxygen consumption in humans, previously shown to have elevated anaplerosis (7), correlated with poorer NAS and necroinflammatory scores. These data are similar to results by Egnatchik et al (26,52), who found that exposure of liver cells to elevated NEFA caused increased TCA cycle flux and oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most importantly, we found that calculated oxygen consumption in humans, previously shown to have elevated anaplerosis (7), correlated with poorer NAS and necroinflammatory scores. These data are similar to results by Egnatchik et al (26,52), who found that exposure of liver cells to elevated NEFA caused increased TCA cycle flux and oxidative stress.…”
Section: Discussionsupporting
confidence: 92%
“…Since GNG mediated by TCA cycle cataplerosis is a significant consumer of hepatic energetics (16), we examined whether suppressing cataplerosis reduces oxidative stress in vitro. H4IIE cells incubated in the presence of high NEFA developed a 2-fold increase in ROS detected by 2′,7′-dichlorofluorescein, which is similar to results reported in primary hepatocytes (26). However, this effect was attenuated when anaplerotic/cataplerotic flux was blocked by the PEPCK inhibitor mercaptopicolinic acid ( Figure 3H).…”
Section: The Journal Of Clinical Investigationsupporting
confidence: 87%
“…Palmitate-induced lipotoxicity may occur through generation of reactive oxygen species (ROS) (97,98). Elevated levels of palmitate compromised the ER's capability to maintain Ca 2+ stores, resulting in the stimulation of mitochondrial oxidative metabolism, ROS production, and ER stress-mediated cellular dysfunction (98).…”
Section: Er Stress and Lipotoxicity In Peripheral Organsmentioning
confidence: 99%
“…Elevated levels of palmitate compromised the ER's capability to maintain Ca 2+ stores, resulting in the stimulation of mitochondrial oxidative metabolism, ROS production, and ER stress-mediated cellular dysfunction (98). It is wellknown that protein misfolding in the ER and subsequent induction of ER stress contribute to ROS production and cellular dysfunction, which can be prevented by antioxidant treatment (29,31,32).…”
Section: Er Stress and Lipotoxicity In Peripheral Organsmentioning
confidence: 99%
“…Although the molecular mechanisms of stearic-acidinduced lipotoxicity are not fully understood, it is evident that enhanced endoplasmic reticulum (ER) stress is a central contributor to lipotoxicity resulting from transcriptional reprogramming [12], activation of c-Jun N-terminal kinase [13], CCAAT/enhancer binding protein homologous protein (CHOP) [14], p53 and mitochondrial apoptosis pathways [15,16]. Importantly, microRNAs (miRNAs), which are involved in post-transcriptional regulation under ER stress, have emerged as key regulators of hepatocyte and cardiac muscle lipotoxicity [17,18].…”
Section: Introductionmentioning
confidence: 99%